The use of Polistes versicolor (Olivier, 1971) in the control of Ascia monuste orseis (Godart, 1819) in kale cultivation - Jacques, Gabriel de Castro; Oliveira, Daniel Cambraia; Souza, Marcos Magalhães de; Silveira, Luís Cláudio Paterno (Revista Agrogeoambiental, 2020)
Social wasps have been successfully utilized as means of biological control, particularly for the larvae of Lepidoptera. Ascia monuste orseis causes devastating effects on the kale, inducing production losses of up to 100%, therefore, requiring stringent control measures. This work aimed testing the species Polistes versicolor as potential means of biological control of A. monuste orseis, during autumn and winter, when the kale crop shows good development. These experiments were conducted at the IFMG - Bambuí Campus, between May and June 2017, during which time four P. versicolor colonies were translocated to artificial shelters constructed in proximity to the kale crop, being registered daily the predation of the social wasp on like of A. monuste orseis caterpillars. The translocation of P. versicolor colonies onto the kale crop during the cold and drought seasons was shown to be ineffective in controlling the A. monuste orseis population. This was because this social wasp exhibited low foraging activity, and therefore a low degree of predation on the target pest; however, it became crucial to assess their activity during the hottest and most humid times of the year, as P. versicolor effectively preys upon the various species among the Lepidoptera.